The use of saffron in depression among nursing students in Indonesia: A quasi-experimental study - Retno Sumiyarini; Khristina Diaz (Universitas Muhammadiyah Magelang, 2023)
Globally, around 17,3% of college students perceived depression. Untreated depression will negatively impact students’ quality of life; moreover, it can trigger students to consume drugs and alcohol or commit suicide. This study aimed to evaluate the effect of saffron on students who perceive depression. This is an experimental, un-blinded study. In this study, 71 nursing students who perceived depression symptoms participated. In the saffron (intervention group), 40 nursing students were voluntarily assigned to receive saffron (5 strands of dried saffron petals, brewed in 200 ml warm water, consumed twice daily, morning and night). In comparison, 31 students (control group) drink regular tea for two weeks. Using the DASS 21 Checklist, we assessed the students at baseline and, after two weeks, completed therapy to measure the outcome. Finally, the data were analyzed using Wilcoxon Test statistical analysis. Saffron had a more significant impact on depression levels among the intervention group. The mean stress scores decreased from 15.4 ± 6.1 to 10.8 ± 5.8 for the saffron group (p < .0001), while for the control group, the depression score slightly increased from 13,74 to 14,52. Our findings suggest that saffron is effective in reducing depression levels among nursing students. Keywords: Depression; nursing care; nursing students; nursing intervention; complementary therapy